Ceramics of the settlement of Rakhat site of IX – the beginning of the XIII centuries (Results of field research in the archaeological complex of Rakhat) (Journal of history, 2021)
The article put into scientifical turn data on archaeological materials obtained in 2021 during the archaeological research of the Rakhat site. This site is located between the cities of Talgar and Issyk a few hundred meters above the route connecting them. A brief history of the study of this extraordinary site has been given by archaeologists, employees of the Issyk Reserve-Museum since 2013, including, collaborative with Chinese colleagues in the period 2017-2019. The main materials – archaeological sources for interpreting the cultural layers of the site are fragments of ceramics of medieval times. The article describes fragments from the excavations of 2021, together with their images. The fragments are interpreted (typologized) – possible forms of medieval kitchen, dining, container vessels belonging to the Karluk and Karakhanid periods are restored. A statistical summary is given of the material discovered during excavations and collected from the modern surface over the years of research by the reserve staff on the site. An analysis of the purpose of these vessels is made in the context of the current state of study of the site.Ceramics is the most massive artifact on almost any archaeological site. Any detectable fragment ofceramics is reliably associated with its own characteristics: pottery school, fine culture, sign system and clay deposit. Thus, it is possible to define an epoch and an ethno-cultural group. A potter is a representa- tive of one of the first creative professions, when household items (ceramic vessels) were obtained from clay, and a fragment of ceramics carries information about its era.Key words: Monument, foothills of Ile Alatau, Rakhat site, Middle Ages, ceramics, typology and statistical analysis.